Sacred witness : rape in the Hebrew Bible - Scholz, Susanne, 1963- (Fortress Press, 2010)
"In Sacred Witness, Susanne Scholz discusses the wide range of rape texts in biblical literature-some that long have troubled readers, others that should have but didn't, such as texts of marital rape, for example, or metaphorical speech about God as rapist. Assuming the androcentric nature of these writings, Scholz asks how we may read these texts in order to find some redemptive meaning for women, children, and men who have been injured by sexual violence and by "cultures of rape." Sacred Witness provides illuminating reflection on some of the most troubling texts in the Hebrew Bible"--Publisher description.